PROPERTIES IDENTIFICATION OF SEED MIXTURES AT THEIR DIVISION INTO VIBRO-CENTRIFUGAL SIEVE SEPARATORS - Kharchenko, S. O.; Kharchenko, F. M.; Pankova, O. V.; Bakum, M. V.; Kharchenko, D. O. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2022)
Modeling the dynamics of loose media particles, which are seed materials, requires the use of the most accurate values of their properties. Seed mixtures properties, which are a heterogeneous environment, depend on the culture, humidity and other factors. Division process of seed material by size on vibrating sieves depends on the shape, size and specific gravity of particles. Viscosity is a generalized parameter that characterizes a loose medium. When using the hydrodynamic analogy of fluidized seed material in modeling processes on a vibro-centrifugal sieve, it is advisable to use the dynamic viscosity coefficient. Сalculations were carried out to determine the dynamic viscosity coefficient for seed materials that differ in shape, size, friction coefficients and specific gravity of particles. The passport design and kinematic parameters of the A1-BCS type vibro-centrifugal separators were used for the calculations. It is accepted that seed material moves along the inner surface of cylindrical sieve with an annular layer of thickness, which depends on the equivalent diameters of seed materials particles of different crops. The speed of seed material movement is directed along the axis of the vertical axis and depends on the radial coordinate. The cylindrical sieve rotates around the vertical axis and performs vertical oscillations along it with amplitude. The properties list of seed material, which are significant in the grounding parameters of particle separation process on cylindrical vibrating sieves of centrifugal grain separators has been established: particle equivalent diameter and weight; coefficient of internal dry friction of seed; correction factor for porosity of the medium; density of the medium layer; dynamic coefficient of particles friction on the sieve surface; height (thickness) of the medium layer. Mathematical calculations confirmed the experimental studies. The discrepancy between the identified and known indicators of properties according to standard and developed methods: seeds of winter wheat, corn, sunflower, rapeseed does not exceed 5%. A significant difference in the vibrоviscosity of agricultural crops seed materials of winter wheat, sunflower, corn and rapeseed was found, which is explained by the particles properties. The obtained data are the basis for adequate modeling of sieve separation processes of seed material particles of seed cleaning machines and separators.